Resilience, parenting stress and burden of parents of children with a diagnosis of a congenital anomaly - Albuquerque, Sara (2016)
The purpose of this study was to assess the parental adaptation, in terms of perceived burden and parenting stress, and to examine the potential influence of parents’ resilience characteristics in their adaptation. The sample consisted of 45 couples, whose child hada diagnosis of disability or congenital anomaly. The assessment protocol included the Resilience Scale for Adults (RSA), the Impact on Family Scale (IOF) and the Parenting Stress Index – Short form (PSI‑SF). The results showed that mothers reported significantly higher scores on Parental distress and fathers reported higher scores on Dysfunctional interaction parents‑child.Regarding perceived burden, no significant differences were found between mothers and fathers. Among both parents, resilience was associated with better adaptation outcomes. Maternal resilience was not significantly associated with the paternal adaptation; however, it was observed that higher levels of paternal resilience were significantly associated with better maternal adaptation. Findings from this study highlight that resilience characteristics may be important determinants in the parental adaptation. These findings also emphasize the need to assess not only mothers and fathersseparately, but also the couple as a unit of analysis, as well as analyse parental resources and the potential cross‑over effects when designing therapeutic interventions.